Developing an effective groundwater monitoring plan for the Kathmandu Valley - Shrestha, Suresh Das; Shakya, Nir; Mishra, Sanjita; Maharjan, Sudan Bikash (Journal of Nepal Geological Society, 2011)
Available with full text.